Multi-Theoretical Organizational Analysis: Determinants of the Success of SIMRS Integration in the Context of Health Organizations - Pratomo, Nugroho Rizki; Putriasni, Chyntia; Purwadhi, Purwadhi; Widjaja, Yani Restiani (ProBisnis : Jurnal Manajemen, 2025)
Background: Hospital Management Information System (SIMRS) integration faces complex challenges that require a deep understanding of organizational dynamics. A comprehensive theoretical approach is needed to identify determinants of successful implementation. Objective: To analyze the determinants of the success of SIMRS integration using a multi-theoretical organizational framework including Systems Theory, Contingency Theory, Technology Acceptance Model, and Organizational Learning Theory. Method: Qualitative research with a case study approach in three type B hospitals in Indonesia. Data were collected through in-depth interviews with 45 respondents, participant observation, and document analysis. Data analysis used thematic analysis with a theoretical framework as a guide. Results: Identification of 12 main determinants of SIMRS integration success categorized into four theoretical dimensions: (1) Systems integration complexity (5 factors), (2) Organizational contingency factors (3 factors), (3) Technology acceptance drivers (2 factors), and (4) Learning capability factors (2 factors). Leadership commitment and user engagement factors are the most significant determinants. Conclusion: The success of SIMRS integration requires a holistic approach that integrates multi-theoretical perspectives of the organization. The developed framework can be a practical guide for hospital management in optimizing SIMRS implementation.